Sheila M. answered • 02/03/13

Friendly College Math Professor - understands students' math anxiety

Hi, Clifford.

You're right when you say that you need to multiply the neg 5 by n and by 2. But be careful with your signs...

-5 * n = -5n

-5 * 2 = -10 (not pos 10)

After you do that you multiply the second grouping by -1 (the one is "understood")

-1 * 3 = -3

-1 * 6n = -6n

Now your new equation looks like this:

-5n - 10 - 3 - 6n = -12n

Once you've taken care of the grouping symbols (the parentheses), you can simplify the left side by combining like terms:

-11n - 13 = -12n

From here, get variable terms on one side and plain number (constant) terms on the other:

-11n - 13 = -12n

+12n +12n

n - 13 = 0

Now add 13 to both sides to get your answer:

n - 13 = 0

+ 13 + 13

n = 13

Hope this helps.

Sheila M.

Glad this helped. =)

03/31/13

Clifford T.

Thank you. My instructor does not always use all the steps because he thinks we know more than we do. this has been a great help.

02/03/13